PROSES REAKSI GLISEROL DAN ASAM BENZOAT DENGAN MENGGUNAKAN KATALIS ASAM SULFAT - Ari Eko Prasetyo; Anggra Widhi; W. Widayat (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Glycerol is by-product of biodiesel making, and therefore requires processing in order to increase its economic value. The products of the glycerol conversion by esterification is commonly used in the food industry, cosmetics industry, polymer industry. This study aims to examine the reaction of glycerol and benzoic acid using sulfuric acid catalyst. Experiments carried out by reacting glycerol and benzoic acid in stirred reactor with a fixed variable Stirrer speed is 200 rpm and the volume of 0.3 ml of sulfuric acid. Temperature variable varies at 60, 65 (0C) and mol ratio between benzoic acid and glycerol varies at 1:1, 2:1, 3:1 and 4:1. Sampling was carried out at regular intervals of 5, 10, 15, 20, 25, 30 minutes. Early stages of the experiment is to dissolve benzoate acid in methanol before reaction can be run in liquid-liquid phase. The highest conversion in the experiments was 64.165% in the glycerol and benzoic acid mole ratio of 1:3 with operating temperatures of 600C. While on the operating temperature of 650C is best hasi was 57.176% with a glycerol and benzoic acid mole ratio of 1:3. The optimum time trial at the highest conversion was 30 minutes. The results of FTIR show a similarity test library IR spectra of samples with concentration of glycerol tribenzoat 41,4%.